Faktor-Faktor yang Memengaruhi Niat Membeli Kosmetik Halal yang Ramah Lingkungan di E-commerce: Perluasan Model UTAUT 2 dengan Variabel Trust dan Label Halal - Lailatul Mufidah; Ach. Yasin (Jurnal Ilmiah Ekonomi Islam, 2026)
Growing public awareness of environmental issues is driving changes in consumer behavior toward choosing more environmentally friendly products, including cosmetics. At the same time, digital advancements have made it easier for consumers to make online purchases through e-commerce. This study aims to analyze the factors that may influence the intention to purchase eco-friendly halal cosmetics via e-commerce among residents of East Java, using an extension of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model that incorporates the variables of trust and halal labeling. A quantitative approach was used. The study used purposive sampling, with a total of 414 respondents. Data analysis was performed using the PLS-SEM (Partial Least Squares - Structural Equation Modeling) method. The results of the study indicate that effort expectancy, facilitating conditions, hedonic motivation, price-value, habit, and trust have a significant positive influence on the intention to purchase eco-friendly halal cosmetics on e-commerce platforms. Meanwhile, performance expectancy, social influence, and the halal label do not significantly influence the intention to purchase eco-friendly halal cosmetics on e-commerce platforms.